2008
DOI: 10.1128/jcm.01931-07
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mycoplasma ovipneumoniae Infection with Population-Limiting Respiratory Disease in Free-Ranging Rocky Mountain Bighorn Sheep ( Ovis canadensis canadensis )

Abstract: Bronchopneumonia is a population-limiting disease in bighorn sheep in much of western North America. Previous investigators have isolated diverse bacteria from the lungs of affected sheep, but no single bacterial species is consistently present, even within single epizootics. We obtained high-quality diagnostic specimens from nine pneumonic bighorn sheep in three populations and analyzed the bacterial populations present in bronchoalveolar lavage specimens of seven by using a culture-independent method (16S rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
117
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 107 publications
(125 citation statements)
references
References 26 publications
7
117
1
Order By: Relevance
“…haemolytica, B. trehalosi, P. multocida, and M. ovipneumoniae have been identified as pathogens associated with pneumonia in BHS (5,9,20,23,27). Of these, M. haemolytica has been shown to consistently induce fatal pneumonia in BHS under experimental conditions (12,19,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…haemolytica, B. trehalosi, P. multocida, and M. ovipneumoniae have been identified as pathogens associated with pneumonia in BHS (5,9,20,23,27). Of these, M. haemolytica has been shown to consistently induce fatal pneumonia in BHS under experimental conditions (12,19,29).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, B. trehalosi and P. multocida are unlikely to be the major pathogens of pneumonia in BHS (35). Experimental inoculation studies have shown that M. ovipneumoniae does not cause fatal pneumonia in BHS lambs (5). Nevertheless, it can predispose adult BHS to M. haemolytica pneumonia (6,14).…”
mentioning
confidence: 99%
“…Bacterial pathogens commonly detected in pneumonic bighorn lungs include Mannheimia (Pasteurella) haemolytica, Bibersteinia (Pasteurella) trehalosi, Pasteurella multocida, and Mycoplasma ovipneumoniae (Miller 2001;Besser et al 2008;Wolfe et al 2010). Of these bacteria, M. haemolytica has been most extensively studied as a cause of fatal pneumonia in bighorns (Foreyt et al 1994;Dassanayake et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The bacterium can be found within the lungs, trachea, and nasal cavity of small ruminants. also Mebratu Asaye et al (2015) isolated many species of bacteria from pneumonic sheep lung but Staphylococcus spp.was the predominant one by percentage of 42.4%on the other hand in this study no detection to P.multocida that is differ from others Rosário Gonçalves (2010) recorded the high mortality rate related to combination of M.ovipneumoniea with P.multocida and Mannheimia haemolytica (the main cause of pneumonia in sheep and goat),which my explained by Besser et al (2008) mentioned that M.ovipneumoniae may act as the only pneumonia pathogen in lamb as it was the predominant one or the primary pathogen which enhances the secondary bacterial infection Post mortem examination, the lesions in the dead animals appear to be the same with Rosário Gonçalves (2010) in epidemiological point of view the deaths were in the summer months (July and August) ( Table 2, Fig 1), the total number of the dead animals are 154 sheep and goats the high percent of deaths occurred in flock 3 in Shrq Aleuaynat by 15% , the high deaths occurred in sheep species by 71.43% while goat species 28.57% the result are agree with Besser et al (2008) who mentioned that M.ovipneumoniae linked to the deaths of bighorn sheep in the Western United States in July 2007.…”
Section: Discussionmentioning
confidence: 66%